(untitled) (Research Journal of Padmakanya Multiple Campus, 2024)
This article explores the narratives of mountaineering expeditions on Mount Everest and Mount Annapurna, highlighting the profound journey of self-discovery and personal transformation, experienced by climbers. It delves into how human hubris turns into trepidation and terror, leading climbers to a humbling realization of their insignificance, which ultimately fosters a transformation into a more compassionate, resilient, and wise being. By employing Edmund Burke’s concept of the sublime, the article captures the awe, wonder, and fear encountered by mountaineers as they confront the immense challenges of their expeditions. The research employs descriptive and analytical methods to examine the personal narratives of the successful summiteers of Mt. Everest and Mt. Annapurna, documenting their experiences and the resulting revelations of self-discovery and transformation.